2019
DOI: 10.3390/ijms20061427
|View full text |Cite
|
Sign up to set email alerts
|

Protein Interactomic Analysis of SAPKs and ABA-Inducible bZIPs Revealed Key Roles of SAPK10 in Rice Flowering

Abstract: As core components of ABA signaling pathway, SnRK2s (Sucrose nonfermenting1–Related protein Kinase 2) bind to and phosphorylate AREB/ABF (ABA responsive element binding protein/ABRE-binding factor) transcriptional factors, particularly bZIPs (basic region-leucine zipper), to participate in various biological processes, including flowering. Rice contains 10 SnRK2 members denoted as SAPK1-10 (Stress-Activated Protein Kinase) and dozens of bZIPs. However, which of the SAPKs and bZIPs pair and involve in ABA signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…It is now clear that, together with SAPK8 and 9, SAPK10 could phosphorylate Tiller enhancer to block the GA signaling with elevated endogenous ABA concentration and retarded seedling growth, which is implicated in the ABA‐mediated inhibition of plant growth (Lin et al ., 2015). SAPK10 is also involved in the ABA‐regulated rice flowering via phosphorylating bZIP77 in the FAC‐MADS15 pathway (D. Liu et al ., 2019; X. Liu et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now clear that, together with SAPK8 and 9, SAPK10 could phosphorylate Tiller enhancer to block the GA signaling with elevated endogenous ABA concentration and retarded seedling growth, which is implicated in the ABA‐mediated inhibition of plant growth (Lin et al ., 2015). SAPK10 is also involved in the ABA‐regulated rice flowering via phosphorylating bZIP77 in the FAC‐MADS15 pathway (D. Liu et al ., 2019; X. Liu et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…bZIPs are typical ABF TFs that can be phosphorylated by SnRK2 in ABA signaling (D. Liu et al ., 2019; X. Liu et al ., 2019). The current study showed that ABA‐inducible bZIP72 is subject to the protein phosphorylation regulation by SAPK10.…”
Section: Discussionmentioning
confidence: 99%
“…Several other bZIP transcription factors are also involved in drought-mediated flowering time regulation in rice, including OsFD1/OsbZIP77 and OsbZIP72 [ 78 , 79 , 80 ]. OsFD1/OsbZIP77 promotes flowering by forming a complex with Hd3a and RFT1 in the shoot apical meristem [ 81 ].…”
Section: Environmental Stresses and Floweringmentioning
confidence: 99%
“…OsFD1/OsbZIP77 promotes flowering by forming a complex with Hd3a and RFT1 in the shoot apical meristem [ 81 ]. In addition to developmental cues, OsFD1/OsbZIP77 expression is also induced by ABA treatment [ 78 ]. Furthermore, OsFD1/OsbZIP77 interacts with the SnRK2 protein SAPK10.…”
Section: Environmental Stresses and Floweringmentioning
confidence: 99%
See 1 more Smart Citation